AI in BIM and Digital Twins for Architecture: Building the Future, Preserving the Past - Rashmi KC Sharma,; Sweta Shrestha, (KEC Journal of Science and Engineering, 2025)
The integration of AI with Building Information Modeling (BIM) and Digital Twin technology is reshaping the architectural landscape, bridging the gap between cutting-edge construction practices and the preservation of cultural heritage. This article explores how AI-driven BIM streamlines construction through predictive maintenance, cost optimization, and real-time project adjustments, enabling the creation of efficient, resilient, and sustainable structures. Simultaneously, digital twin technology, powered by AI, offers new avenues for historic preservation by producing data-rich, 3D models that allow for precise monitoring and virtual restoration of heritage sites. By examining real-world applications in both modern buildings and historic landmarks, this article demonstrates how AI’s role in architecture not only advances building practices but also safeguards architectural history for future generations.